ADULT LEARNERS’ LANGUAGE ACQUISITION: A CASE STUDY OF IN-HOUSE TRAINING OF COMPANY “X” JAKARTA - Datu, Yerly Arnold (Politeknik Ubaya, 2024)
The acquisition of English proficiency among adult learners is essential in today's globalized world, where English serves as the lingua franca of international business and communication. The demand for English proficiency extends beyond external business interactions to internal organizational processes, where effective communication within multicultural teams is crucial for collaboration and productivity. To thrive in the interconnected global economy, Indonesian companies must invest in English language training initiatives to equip their workforce with the necessary skills to navigate diverse work environments successfully. This descriptive qualitative study employing a case study approach aims at describing language acquisition of participants attending an in-house training called Business English program, obstacles faced, strategies applied as well as results obtained. The study also provides an overview of two analyses concerning challenges and strategies in adult language acquisition. The findings summarize participants’ profiles, revealing a gender skew towards females and varying levels of confidence despite strong motivation levels. Notably, it highlights that 75% of participants displayed mediocre speaking ability, while 25% exhibited low proficiency. Additionally, 75% had low confidence levels, contrasting with one participant's high confidence. All participants demonstrated strong motivation. Furthermore, improvements in fluency and accuracy skills are evident across participants, with scores increasing by an average of 7.9%. This indicates the effectiveness of instructional strategies in enhancing language proficiency. The analysis underscores the complex interplay between participant characteristics, instructional approaches, and language learning outcomes, offering insights for educators to tailor pedagogical strategies and create supportive environments conducive to adult language acquisition.